A three dimensional non-hydrostatic model for turbulent air flow - Hai, Duong Ngoc; Duc, Nguyen The (Vietnam Journal of Mechanics, 2000)
A finite-volume code is developed to compute the turbulent airflow over small- scale complex terrain. A pressure-correction algorithm is used to solve the three-dimensional non-hydrostatic flow equations. The turbulent transport is simulated by the k- € model using some modifications suitable for atmospheric boundary-layer application. As an example, the model is used to simulate the flow-field around a cubical building. The same flow as a towing-tank experiment of USEPA was simulated using our code. These simulations show that, the model was capable of simulating recirculation zones behind the building. The results of calculation are also compared with available measurement data.